Учет явления гистерезиса при численном моделировании периодического электромагнитного поля в ферромагнетике - Петухов, И.С. (Технічна електродинаміка, 2012)
The analysis of one-dimensional hysteresis models in a ferromagnetic medium was done and solvability criteria for the of the finite element method simulation of a periodic electromagnetic field using the method of time harmonics was formulated. There was made the assumptions for the mathematical model of two-dimensional electromagnetic field in a ferromagnetic medium taking into account the hysteresis losses under symmetrical magnetization